Biological nitrogen fixation in trees in agroecosystems: twenty years of biological nitrogen fixation research in Africa. - Danso, S.K.A. (1992)
With the low input of fertilizers into African farming systems, it is necessary to harness biological nitrogen fixation to its fullest extent. The greatest potential, at least in the short term, lies in nitrogen fixation in grain and pasture legumes and in nitrogen-fixing trees. To maximise nitrogen fixation in these plants and under various cropping systems requires intensified research. Inoculation techniques and inoculum production in Africa are not yet advanced, and this is unlikely to change until unequivocal proof for their need has been established. The present indication is that several indigenous grain legumes do not respond to inoculation. This has been interpreted to mean that, for locally cultivated grain legumes, highly competitive and effective Rhizobium strains abound in the soils of Africa. More research is needed to prove these claims. Studies on the ecology ofRhhobium need to be intensified, with some mechanistic studies to understand the possible factors underlying competition between Rhizobium strains. For most nitrogen-fixing trees, although the microbial component (Rhizobium or Frankia) has been little studied in Africa, there is a strong indication that rhizobial or Frankia inoculation will be most beneficial.